Konsep Ketuhanan Dalam Teks Tattwa Sangkaning Dadi Janma - Putu Cory Candra Yhani; Putu Sri Marselinawati; Kadek Agus Wardana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The Hindu concept says that humans consist of 2 human elements, namely physical and spiritual. The body is the body, the human body, while the spiritual is the eternal, eternal essence of God, which is called Atman. Living in a community, besides providing a sense of security, also through that community, humans can develop their resources maximally in order to achieve a prosperous life through social exchange and of course good communication therein, while as a religious being, human life cannot be separated from its relationship with God. A lontar that discusses the essence of God in human body parts, namely Tattwa Sangkaning Dadi Janma, in the Tattwa Sangkaning Dadi Janma text teachings about kamoksan, containing teachings about the nature of Shiva, about the origin and purpose of being human. The substance which is so thick that binds the elements from the toe to the head of the human is discussed in the text. The teachings that are encapsulated through divine symbols are translated into parts of the body, making the human seem the most perfect among other creatures.